Excess mortality, causes of death and life expectancy in 270,770 patients with recent onset of mental disorders in Denmark, Finland and Sweden. - Merete Nordentoft; Kristian Wahlbeck; Jonas Hällgren; Jeanette Westman; Urban Osby; Hassan Alinaghizadeh; Mika Gissler; Thomas Munk Laursen (PLoS ONE)
Background Excess mortality among patients with severe mental disorders has not previously been investigated in detail in large complete national populations. Objective To investigate the excess mortality in different diagnostic categories due to suicide and other external causes of death, and due to specific causes in connection with diseases and medical conditions. Methods In longitudinal national psychiatric case registers from Denmark, Finland, and Sweden, a cohort of 270,770 recent-onset patients, who at least once during the period 2000 to 2006 were admitted due to a psychiatric disorder, were followed until death or the end of 2006. They were followed for 912,279 person years, and 28,088 deaths were analyzed. Life expectancy and standardized cause-specific mortality rates were estimated in each diagnostic group in all three countries. Results The life expectancy was generally approximately 15 years shorter for women and 20 years shorter for men, compared to the general population. Mortality due to diseases and medical conditions was increased two- to three-fold, while excess mortality from external causes ranged from three- to 77-fold. Mortality due to diseases and medical conditions was generally lowest in patients with affective disorders and highest in patients with substance abuse and personality disorders, while mortality due to suicide was highest in patients with affective disorders and personality disorders, and mortality due to other external causes was highest in patients with substance abuse. Conclusions These alarming figures call for action in order to prevent the high mortality.